2020
DOI: 10.1111/cns.13461
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diagnostic criteria and red flags of myelin oligodendrocyte glycoprotein encephalomyelitis in a clinical routine cohort

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…International comparative studies of different MOG-IgG1 assays have shown that live cell–based assays yield the highest specificity for MOGAD . However, MOGAD is rare, and indiscriminate testing for MOG-IgG1 may lead to false-positive results despite high specificity . The positive predictive value (PPV), which provides the likelihood that a positive test result is truly positive for the disease of interest, is arguably of greater clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…International comparative studies of different MOG-IgG1 assays have shown that live cell–based assays yield the highest specificity for MOGAD . However, MOGAD is rare, and indiscriminate testing for MOG-IgG1 may lead to false-positive results despite high specificity . The positive predictive value (PPV), which provides the likelihood that a positive test result is truly positive for the disease of interest, is arguably of greater clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“… 68 , 75 Given the overall rarity of double positive cases based on the results of the larger studies, and considering the superior specificity of the AQP4-IgG test compared to the MOG-IgG test, and that a reliable cell-based-assay (CBA) for detecting MOG-IgG has been available just recently (2017), there is a high possibility that most of the double positive cases may likely be AQP4-IgG + NMOSD with false positive MOG-IgG test results, especially in reports made before this time with using enzyme-linked immunosorbent assay (ELISA). 68 , 75 …”
Section: Discussionmentioning
confidence: 99%
“…2,3 Although typical criteria for multiple sclerosis (MS) are usually not met, 1 clinical differentiation of MOGAD and MS may still be difficult. 4 MOGAD cannot be considered as equivalent to aquaporin 4 (AQP4)-IgG-seronegative neuromyelitis optica spectrum disorder (NMOSD) 5 due to different epidemiologic, clinical, radiographic features and outcome 6 and most interestingly remarkable immunologic differences. [7][8][9] Retrospective studies suggest that treatment strategies that work well in MS and NMOSD, e.g., targeting CD20 + B cells, are not similarly effective in MOGAD.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 Although typical criteria for multiple sclerosis (MS) are usually not met, 1 clinical differentiation of MOGAD and MS may still be difficult. 4 …”
mentioning
confidence: 99%